Overview of Romania 802.11Wireless Security & Statistics - Liviu Leca, Cristian (EAI Endorsed Transactions on Security and Safety, 2017)
This paper presents a study of wireless network security and statistics in Romania aimed at raising public awareness on security issues and highlighting the prevalence of known vulnerabilities in commercial equipment. The data used for the study consist of wireless network broadcast data acquisitioned by the technique of war-driving. In order to ensure a thorough overview, the data collected includes more than 100000 unique wireless networks gathered in Bucharest, major urban areas and the surrounding rural areas. The results of the study cover security protocol usage, the percentage in which known vulnerabilities are still deployed in wireless networks and statistics regarding channel and band usage, common SSIDs in Romania, top equipment manufacturers and the situation of provider wireless access points. The study also shows that provider wireless access points on average oer better security than private networks.